Pemanfaatan Aplikasi Tiktok dalam Mata Pelajaran PAI sebagai Media Pembelajaran Inovatif Era Digital - Fauziyah, Nurul; Afendi, Achmad Ruslan; Saputra, Muhammad Rohan; Kamaria, Kamaria (Borneo Journal of Islamic Education, 2023)
Abstract Modern times force Islamic religious education to develop quickly, efficiently and effectively, so that PAI learning is not left behind with the digitalization of the increasingly advanced world. Learning facilities in the current era of digital globalization should be adapted to technological advances. The use of technology as a learning medium is one to increase the interest in learning students so that teaching is not always monotonous. This study aims to illustrate the use of the TikTok application as a PAI learning medium. A qualitative descriptive research design was used in this study. The TikTok application is the main topic in this study, with discussions about the use of the TikTok application as a learning medium. This information is collected using a type of descriptive method of analysis using research facilities in the form of journals. The results of the study stated that the use of the TikTok application with its ease of use and diverse functions can be useful as a means in an innovative and interactive learning process. But in addition to positive influences, there are also negative influences in the use of TikTok, so it is hoped that educators can be creative and careful in using these media to run effectively and students are wise in using it Keywords : TikTok, Digital Age, Learning Media, Islamic Education Abstrak Zaman modern memaksa Pendidikan Agama Islam (PAI) berkembang dengan cepat, efisien dan efektif, sehingga pembelajaran PAI tidak ketinggalan dengan digitalisasi dunia yang semakin maju. Sarana belajar di era globalisasi digital saat ini layaknya disesuaikan dengan kemajuan teknologi. Pemanfaatan teknologi sebagai media pembelajaran yaitu menjadi salah satu untuk meningkatkan ketertarikan minat belajar peserta didik agar pengajaran nya tidak selalu monoton. Penelitian ini bertujuan untuk menggambarkan pemanfaatan aplikasi TikTok sebagai media pembelajaran PAI. Metode penelitian deskriptif kualitatif digunakan dalam penelitian ini. Aplikasi TikTok merupakan topik utama, dengan hal bahasan tentang pemanfaatan aplikasi TikTok sebagai media pembelajaran. Informasi ini dikumpulkan menggunakan jenis metode deskriptif analisis menggunakan sarana penelitian berupa jurnal. Hasil penelitian menyatakan bahwa penggunaan aplikasi TikTok dengan kemudahan penggunaan dan fungsinya yang beragam dapat bermanfaat sebagai sarana dalam proses belajar yang inovatif dan interaktif. Tetapi selain pengaruh positif terdapat pula pengaruh negative dalam pemanfaatan TikTok, sehingga diharapkan bagaimana pendidik dapat kreatif dan cermat dalam penggunaan media tersebut agar berjalan dengan efektif dan peserta didik bijak dalam menggunakannya. Kata Kunci : TikTok, Era Digital, Media Pembelajaran, Pendidikan Agama Islam